APLIKASI PEMESANAN BARANG DI BENGKEL LAS MUTIARA BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK CODEIGNITER - Wika Purbasari; Joko Purnomo; Riana Safitri; Della Sinta Romadoni (LPPM STMIK Widya Utama, 2023)
Abstract— Bengkel Las Mutiara is a micro-enterprise that operates in the field of services that provide services for the manufacture of metal products and welding. This business sells items such as iron gates, iron fences, canopies, flower pots and others. However, in the process of recording transactions, they still use manual methods, namely using paper media. It has a high risk because the paper is easily damaged and lost. Therefore, in this research, a Website -based Goods Ordering Application was designed in the Pearl Welding Workshop using the CodeIgniter Framework. In its development, this application applies a prototyping method that consists of several steps, namely identify basic requirements, develop initial prototype, user review, and revice and echance the prototype. This application was tested using the Black Box Testing product test method and benefit testing using ULEA attributes. From the recapitulation of the product test value, the overall valid value is obtained and obtained a value above 0.3 on the validity test. Then based on the results of the benefit test obtained the highest percentage on the aspect of Useability and Learnability which is 97.75%. This shows that the Application for Ordering Goods in a Website-Based Pearl Welding Workshop Using the Codeigniter Framework is useful and acceptable.